The Age of Macquarie - Broadbent, James; Hughes, Joy.; Historic Houses Trust of New South Wales (Carlton, Vic. : Melbourne University Press in association with Historic Houses Trust of New South Wales, 1992)
p. 32-34 brief discussion of Aboriginal contacts with colonisers : employment supplying fish, washing spirit casks in return for alcohol; mention of Macquarie's paternalism : provison of farm for Bungaree at Middle Cove, land at Blacktown for Nurragingy and Colebee, school for Aboriginal children at Parramatta; disinterest of missionaries and colonial clergy in Aborigines; Increasing violence between settlers and Dharug, Dharawal and Gundangara; Macquaries's order to capture and kill Aborigines on settlers land during drought of 1816.
Includes index.
Bibliography: p. 185-188.
Keywords: Macquarie, Lachlan, -- 1761-1824.; Race relations - Representation - Art; Settlement and contacts - Colonisation - 1788-1850.; Dharug / Daruk / Darug people (S64) (NSW SI56-05); Gundungurra / Gundungura /Gandangara people (S60) (NSW SI56-09); Race relations; Dharawal / Tharawal / Dariwal people (S59) (NSW SI56-09); Religions - Christianity - Missionaries; New South Wales -- History -- 1788-1851.; New South Wales -- Social conditions -- 1788-1851.; New South Wales (NSW); Parramatta (W Sydney NSW SI56-05)